Eksplorasi Peran Kader Posyandu Terhadap Capaian Program Puskesmas Dalam Menurunkan Kejadian Stunting: Eksplorasi Peran Kader Posyandu terhadap Capaian Program Puskesmas dalam Menurunkan Kejadian Stunting - Chabibah, Ike Fitrah Atul; Agustina, Rakhmawati (Universitas Airlangga, 2023)
Background: Cadre Management is an implementation of the 3rd pillar of handling stunting. The role of good cadres influence the toddlers nutritional status because they become motivators and educators. Through Strength, Weakness, Opportunity, Threat (SWOT) analysis, cadre is an appropriate strategy to reduce stunting. Objectives: To explore the role of cadres through Lawrence Green Theory in the stunting reduction program in the Wori Community Health Center. Methods: Qualitative research with a case study approach in the Wori Community Health Center working area. Total informants were 15 and they were selected by using purposive sampling. Data collection techniques used in-depth interviews, Focus Group Discussion (FGD) and observation. The research instrument used interview guides, camera and voice recorders. Data processing used open code. Results: The predisposing factors are cadre's motivation and skills to reduce stunting rates. The supporting factors are community health centers and village supports. The obstacles are mothers with stunted toddlers received information difficulty and absence in Posyandu, but this problem can be overcome by cadres' communication skills. Conclusions: The role of cadres is important and strategic to reduce stunting. The internal and external factors support keep cadres enthusiastic in carrying out their duties. The importance of regular training and refreshing can improve their knowledge.